PEMBERDAYAAN MASYARAKAT DESA BERBASIS POTENSI LOKAL DESA WAJOK HILIR - Sutriyadi, Yosia; Marsalena, Weni Sentia (Dianmas Bhakti: Jurnal Pengabdian pada Masyarakat, 2025)
Community Service Program (KKN) is a learning process for students through various hands-on activities within the community. Students strive to become part of the community and actively and creatively engage in its dynamics. Community Service Program (KKN) is a form of community service by university students through empowerment assistance, training, counseling, mentoring, and assistance, aimed at raising awareness of their potential, as well as helping to improve quality of life and development. Students will gain generative skills in the form of life skills. Observations are conducted through discussions with village officials and field observations. This KKN program aims to empower village communities through waste management programs, coconut oil production, and social education programs such as promoting anti-bullying and environmental cleanliness. Implementation methods include initial observation, discussions with village officials, collaborative program implementation, and evaluation of results with the community. Results from the program indicate increased community participation in maintaining environmental cleanliness, utilizing local potential in the form of coconut oil production, and a better understanding of the dangers of bullying. Challenges encountered included limited facilities, a short implementation timeframe, and differing perceptions between parties, but these were overcome through open communication and effective collaboration. This activity provided valuable experience for students and made a tangible contribution to the development and empowerment of rural communities.